Hubungan Praktik Keterampilan Mengajar (Pkm) Terhadap Minat Mahasiswa Pendidikan Tata Rias Dalam Mengikuti Program Pendidikan Profesi Guru (PPG) - Nadhira Esthiningtyas; Sitti Nursetiawati; Lilis Jubaedah (Peneliti.net, 2023)
Teaching Skills Practice (PKM) is one of the courses that must be taken by students of the Cosmetology Education Study Program (S1) as training to apply learning theory that has been obtained from Basic Education Courses and Learning Courses. PKM is included in training that can help students who have an interest in becoming teachers so that they are trained to teach students. According to Nurhidayah (2017: 144) Interest can simply be interpreted as a high tendency and enthusiasm or a great desire for something, so that students who have an interest in becoming teachers will be encouraged to take part in Teacher Professional Education. This study aims to determine whether there is a relationship between Teaching Skills Practice (PKM) and the interest of Cosmetology Education students at Jakarta State University in participating in the Teacher Professional Education Program (PPG). The research method used is a quantitative approach with the sampling technique used is Simple Random sampling. Based on a population of 81 people with a confidence level of 95%, a total sample of 67 people was obtained who were cosmetology education students at UNJ class of 2018 and 2019. The data was processed using the product moment correlation test and T test. Based on the product moment correlation test, the significance value was 0.001 < 0.05 so the data is said to be correlated. The Pearson correlation value is 0.608 and the t-test results show that the significance value of the PKM (X) relationship to Interest in participating in PPG (Y) is 0.001 <0.05 and the t-count value is 6.174 > the t-table value is 1.997, so Ho is rejected and Ha is accepted, which means there is a significant relationship between PKM and interest in participating in PPG.